Testing social identity models of collective action in an Iranian environmental movement. (13th April 2021) - Keshavarzi, Saeed; McGarty, Craig; Khajehnoori, Bijan
Abstract: The social identity model of collective action (SIMCA) and the encapsulation model of the social identity of collective action (EMSICA) are well‐known models that have been applied to protest action. The current study tests the predictive value of the core constructs in the models (social identification, perceived injustice and group efficacy) in a peaceful pro‐environmental program. Specifically, we sought to answer whether the two models provide equally good accounts of (self‐reported) past participation and of intended participation. To do so, we conducted a survey of 382 participants of a sustained environmental collective action program (Nature Cleaners) in Iran. Our findings underlined the important role of social identification in predicting environmental action. The results also showed that SIMCA was more relevant for intentions to participate, whereas paths specified by EMSICA better predicted past participation. The results provide a demonstration of the applicability of collective action models to the domain of pro‐environmental action in the Iranian cultural context where collective action is rarely studied. Overall, the findings highlight the importance of studying collective action in a wider range of situations and contexts.